2018
DOI: 10.1097/md.0000000000010353
|View full text |Cite
|
Sign up to set email alerts
|

Companied P16 genetic and protein status together providing useful information on the clinical outcome of urinary bladder cancer

Abstract: SPEC P16/CEN3/7/17 Probe fluorescence-in-situ-hybridization (FISH) has become the most sensitive method in indentifying the urothelial tumors and loss of P16 has often been identified in low-grade urothelial lesions; however, little is known about the significations of other P16 genetic status (normal and amplification) in bladder cancer.We detected P16 gene status by FISH in 259 urine samples and divided these samples into 3 groups: 1, normal P16; 2, loss of P16; and 3, amplified P16. Meanwhile, p16INK4a prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In addition, p16 is a cyclin dependent inhibitor (CDI), which can negatively regulate the cell cycle by inhibiting CDK (50,52,53). The inactivation of the p16 gene will lead to excessive cell proliferation (54). Thus, we hypothesized that p16 may affect cell proliferation in OS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, p16 is a cyclin dependent inhibitor (CDI), which can negatively regulate the cell cycle by inhibiting CDK (50,52,53). The inactivation of the p16 gene will lead to excessive cell proliferation (54). Thus, we hypothesized that p16 may affect cell proliferation in OS.…”
Section: Discussionmentioning
confidence: 99%
“…Feng et al (9) found that when the expression level of p16 is blocked, it leads to dominant binding between cyclin D1 and CDK4 and continuous cell proliferation, thus resulting in tumors. According to the study of Pu et al (10), p16 is a predisposing gene of cardiac carcinoma, and it has been shown in several animal models that the p16 expression level in cardiac carcinoma tissues is significantly reduced. However, the correlation of p16 and cyclin D1 with incidence and prognosis of cardiac carcinoma remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Hashmi et al concluded that high p16 expression was associated with higher grade and muscle invasion [ 58 ]. Some authors found that neither p16 gene status nor the p16 protein expression alone can be nominated as an independent predictor for urothelial carcinomas, but combining protein and gene status together provides useful information on such clinical outcomes of these patients [ 59 ]. We did not find a significant difference between MIBC and NIBC or between both grades except when differentiating between the papillary group and non-papillary, where the papillary lesions showed a significant difference between p16 expression in high grade compared to the low grade and in MIBC versus NMIBC which may raise the attention of histological pattern significance in conventional UCs.…”
Section: Discussionmentioning
confidence: 99%